A CRITICAL REVIEW OF PERATURAN PEMERINTAH REPUBLIK INDONESIA NOMOR 70 TAHUN 2020 CONCERNING THE IMPLEMENTATION OF CASTRATION FOR SEXUAL CRIMES: IN THE PERSPECTIVES OF MAQASHID SHARIA - Luciana Anggraeni (IAIN Bone, 2022)
This research was conducted to analyze the implementation of the law of castration from the perspective of Maqashid Syariah. In Indonesia today there are many criminal acts of rape against women and children. As an alternative punishment with castration as formulated in Law Number 70 of 2020. The method used is normative juridical research, namely research to find legal doctrines or principles, ijma’ (opinions of scholars), therefore in this study the author tries to understand the conversation about sexual deviation, especially those that discuss the application of castration sanctions against sex offenders. This research is a juridical normative research which is viewed from the perspective of Maqashid Shari'ah. In Islamic law, punishment for perpetrators of sexual crimes is given in the form of stoning and whipping. Castration punishment is not in accordance with Maqashid Shari'ah because it can damage human beings which is contrary to the hifdzun of the nafs. First, Islamic sharia has strictly prohibited castration on humans, without any difference of opinion (khilafiyah) among the fuqaha. Second, in terms of the castration method used is the injection method. Third, that which is injected is the hormone estrogen, the law is also haram, because it causes the castrated male to have physical characteristics like women. Based on the 3 reasons, it is unlawful to impose castration on perpetrators of sexual crimes.